Effect of individualised strength and plyometric training on the physical performance of basketball players - Barrera-Domínguez, F. J.; Almagro, B. J.; de Villarreal, E. S.; Molina-López, J. (European Journal of Sport Science, 2023)
The aims of this study were to examine the effects of eight weeks of individualised force-velocity imbalance (F-Vimb) training on physical performance in basketball players and to analyse the differences in physical performance between two periods of time (four to eight weeks) with this training. Thirty male players (age, 22.8 ± 5.68 years; height, 1.87 ± 0.07 m; body mass, 86.3 ± 11.1 kg) were divided into an intervention group (INT, n = 15), who performed an individualised training based on individual F-Vimb; and a control group (CON, n = 15), who underwent a non-individualised training programme; both groups performed two days/week of intervention and the same pre-season basketball training. At baseline, at four weeks, and at eight weeks of intervention, an assessment was performed including countermovement-jumps, unilateral drop jumps, triple hop test, force-velocity profile, sprint and change of direction (COD). At four weeks, the INT showed improvements in sprint and vertical jumping actions (=3.76%, ES =0.44, p = 0.02). At eight weeks, the INT continued to improve vertical jumping actions (p < 0.05) and showed improvements in horizontal jumping (6.80%, ES = 0.45, p < 0.01) and COD (=2.99%, ES =0.96, p < 0.01). A significant reduction in F-Vimb was observed for INT (ES = 0.77, p = 0.01). In contrast, none of these changes were observed in CON. Thus, an individualised F-Vimb training intervention improved physical performance after eight weeks, with changes in sprint and vertical jump after first four weeks. Basketball coaches should optimise the force-velocity profile and improve the performance in sport-related actions as jumping and changing direction.